Peptic ulcer rebleeding in patients with and without chronic kidney disease - Guzmán Calderón, Gerly Edson (2018)
Objective: To determine if rebleeding in peptic ulcer disease (PUD) in patients with chronic kidney disease (CKD) is greater than in patients without CKD hospitalized in the Digestive Bleeding Unit of the Hospital Nacional Edgardo Rebagliati Martins. Materials and methods: An observational, analytical, retro-prospective, case-control study was performed in patients >18 years with rebleeding in PUD, admitted to the Digestive Hemorrhage Unit of the Hospital Nacional Edgardo Rebagliati Martins during 1 year. Results: Out of 146 patients, 26 % were female and 74 % were male. The mean age was 65.47 ± 17.95 years. The cases (PUD with CKD) consisted of 34 patients and the controls (PUD without CKD) consisted of 112 patients. The causes of rebleeding were duodenal ulcer (53 %) and gastric ulcer (47 %). The odds ratio (OR) of rebleeding in patients with CKD was 6.43 times higher than in patients without CKD. Rebleeding in patients with CKD was 41.1 % and in patients without CKD it was 9.8 %. The type of ulcer with the greatest rebleeding was type IIa in both groups. Ninety-four percent (94 %) of the patients were discharged, and 2.7 % were referred to surgery. The total mortality rate was 2.7 %, and the mortality rate in patients with CKD was 5.8 % (p = 0.2). Conclusions: The OR of peptic ulcer rebleeding in patients with CKD is 6.43 times higher than in patients without CKD. Rebleeding in peptic ulcer disease in patients with CKD was 41.1 %, whereas in patients without CKD it was 9.8 %.